Compact Single-Shot Dual-Wavelength Interferometry for Large Object Measurement with Rough Surfaces - Yizhang Yan; Suhas P. Veetil; Pengfei Zhu; Feng Gao; Yan Kong; Xiaoliang He; Aihui Sun; Zhilong Jiang; Cheng Liu (Photonics, 2024)
Single-shot dual-wavelength interferometry offers a promising avenue for surface profile measurement of dynamic objects. However, current techniques employing pixel multiplexing or color cameras encounter challenges such as complex optical alignment, limited measurement range, and difficulty in measuring rough surfaces. To address these issues, this study presents a novel approach to single-shot dual-wavelength interferometry. By utilizing separated polarization illumination and detection, along with a monochromatic polarization camera and two slightly different wavelengths, this method enables the simultaneous recording of two frames of separated interferometric patterns. This approach facilitates straightforward optical alignment, expands measurement ranges, accelerates data acquisition, and simplifies data processing for dual-wavelength interferometry. Consequently, it enables online shape measurement of large dynamic samples with rough surfaces.